2022
DOI: 10.1177/23779608221074655
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and The Relationship of Workplace Bullying and Nurses Turnover Intentions: A Cross Sectional Study

Abstract: Introduction: Sustaining a healthy work environment is a major challenge for health care organizations worldwide. Nursing professionals are often exposed to workplace bullying, which imposes serious challenges to nursing retention. Objectives: To determine the prevalence of workplace bullying and turnover intention among nurses, and to investigate the relationship between workplace bullying and nurse turnover. Methods: A cross-sectional correlational design. Convenience sampling was applied, whereby 347 nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 44 publications
(55 reference statements)
3
31
0
1
Order By: Relevance
“…This is an alarming rate, especially considering that exposure to workplace bullying is closely related to negative nurse outcomes such as work disengagement and burnout (Sauer, 2018; Serafin et al, 2022). According to the American Nurses Association (ANA) COVID‐19 impact assessment (2022), 66% of the nurses reported an increase in bullying at work during the pandemic and suggested that deteriorating work conditions during the pandemic were related to increased bullying (al Muharraq et al, 2022; Clegg, 1993; Huntington & Gilmour, 2001; Hutchinson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an alarming rate, especially considering that exposure to workplace bullying is closely related to negative nurse outcomes such as work disengagement and burnout (Sauer, 2018; Serafin et al, 2022). According to the American Nurses Association (ANA) COVID‐19 impact assessment (2022), 66% of the nurses reported an increase in bullying at work during the pandemic and suggested that deteriorating work conditions during the pandemic were related to increased bullying (al Muharraq et al, 2022; Clegg, 1993; Huntington & Gilmour, 2001; Hutchinson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Bullying may then become invisible or go unrecognized and may be reinforced further, if the target views the bullying as a legitimate form of discipline or feels they are deserving of the treatment. In these cases, victimized nurses can remain silent and passive toward their bullying experience and might then repeat the bullying toward others (al Muharraq et al, 2022). Similarly, Roberts (1994) explained that nurses, as an oppressed group with limited power, repeatedly bully each other to release their aggressive energy and perceived inability to resist the oppressor.…”
Section: Introductionmentioning
confidence: 99%
“…Review of historical and recent studies showed workplace bullying as one of the key determinants of turnover intention. Al Muharraq et al (2022) conducted that there was a strong correlation between bullying in the workplace and employees' intentions to leave their jobs in Saudi Arabia's health sector. Additionally, recent research has shown that workplace bullying is a significant contributor to employee turnover (Coetzee & van Dyk, 2018;Öcel & Aydın, 2012).…”
Section: Workplace Bullying and Turn-over Intentionmentioning
confidence: 99%
“…Furthermore, bullying has generally been deemed as a type of psychological rather than physical violence and is categorized into four types: isolation from work, attack on professional status, attack on personality, and direct negative behaviors (Dilek & Aytolan, 2008 ). It is crucial to note that workplace bullying is associated with a range of adverse outcomes for nurses, such as leaving a job and experiencing psychological problems (Bambi et al, 2019 ; Al Muharraq et al, 2022 ). However, few studies have examined whether and how workplace bullying could increase suicide ideation and attempts among nurses.…”
Section: Introductionmentioning
confidence: 99%